Znaczenie materiałów włókienniczych dla poprawy jakości życia osób długotrwale unieruchomionych w świetle badań własnych - Witczak, Ewa; Cieślak, Małgorzata; Śledzińska, Katarzyna; Lao, Marek; Gromadzińska, Ewa (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The problem of bedsore formation and treatment of long-term immobilized people has a high social significance. Bedsores pose a serious medical and economical problem. The group exposed to the risk of bedsore formation includes, among others, persons working in a sitting position and moving in a wheelchair. Improvement of work conditions at worksites of disabled people or immobilized ones may affect the increase of work activity of this group of people. Lack of bioactive properties and physiological comfort of seats result in infections and dermatological diseases. In the current used seats the fire hazard and static electricity properties are also omitted. Therefore, it is important to develop new functional textiles design for seats and their comprehensive research. Such designed seats may provide appropriate conditions of physiological comfort between the body and the substrate material and limit the risk of bedsore formation. Methods usually applied for clothing products test are improper for assessment the suitability of textile structures for the top layer of anti-bedsore seats in terms of physiological comfort. They must be tailored to the specificity of seats, taking into account the heat and moisture transport under conditions of simulated deformation of the textile system and also the pressure distribution during usage. The research methodology should take into account the analysis of pressure forces, thermal insulation, air and moisture transport in appropriately distributed pressure and the aspect of the safety of use. According to the developed methodology a new model of 3D structures for the top layerof an anti-bedsore seat were tested. These structures are characterized by spatial construction and elasticity of thickness. Due to such construction, regardless of the pressure force during using, there are spaces enabling transfer of heat and moisture excess from the body – seat system. The developed solutions in combination with bioactive function, flame resistancy and antielectrostatic features represent the new quality in materials for seats. The research methodology enables comprehensive evaluation of textile – upholstery systems in the aspect of anti-bedsore prevention and may be used in the design and evaluation of textile structure for new generation seats for long-term immobilized people
Keywords: anti-bedsore prevention; textile structure; seats for disabled persons